Perancangan Antena Mikrostrip Dual Band Profil Rendah Menggunakan Teknik DGS Dan Meander Line Untuk Aplikasi GNSS - Sihombing, Panangian Mahadi (Teknologi Rekayasa Jaringan Telekomunikasi, 2021)
Some of the parameters that are considered to measure GNSS antenna performance are polarization, polarization, bandwidth, return loss and antenna dimensions. This study aims to design a low profile dual band microstrip antenna using the Defected Ground System (DGS) and Menader Line (ML) techniques for GNSS applications. In this research, the DGS technique is used to increase the bandwidth while the ML technique is used to reduce the antenna dimensions. This antenna design uses a FR4 Epoxy substrate with a thickness of 1.6 mm. To design and analyze the antenna, the CST Studio Suite 2016 simulator is used. The simulator is equipped with an optimizer feature that can optimize antenna parameters. Based on the design results, an antenna with a size of 183.6 x 183.6 x 1.6 mm3 has been produced. The antenna works in dual band, namely in the band 1247 - 1294 MHz (bandwidth - 3.70% BW) for radio navigation satellite services Glonass (G2) and Galileo (E6). And in the band 1539-1606 MHz (4.26% BW) for the Galileo (E1) flight radio navigation service, Compass and GPS (L1). Keywords: Global Navigation Satellite System (GNSS), low-profile dual-band microstrip antenna, Defected Ground System (DGS) dan Meander Line (ML).